Ability to Suppress TGF-β-Activated Myofibroblast Differentiation Distinguishes the Anti-pulmonary Fibrosis Efficacy of Two Danshen-Containing Chinese Herbal Medicine Prescriptions - Shao, Rui; Wang, Fu-jiang; Lyu, Ming; Yang, Jian; Zhang, Peng; Zhu, Yan (Frontiers in Pharmacology, 2019)
Background: Idiopathic pulmonary fibrosis (IPF) is a devastating lung disease with limited treatment options. It also leads to progressive respiratory failure, which subsequently affects the heart functionality, a pathological heart-lung interaction increasingly noticed and defined as pulmonary-heart disease (PHD). Traditional Chinese medicine (TCM) theory for treating “phlegm-stasis cementation syndrome” may suggest a possibility of treating PHD complication with Chinese medicine prescriptions previously used for cardiovascular diseases. Methods: Here, we evaluate the efficacies of two compound Chinese medicine prescriptions, Danlou prescription (DLP) and Danhong prescription (DHP), which share a common herbal component, Salvia miltiorrhiza (Danshen)，on pulmonary fibrosis. Severity grades of Bleomycin (BLM)-induced pulmonary fibrosis were assessed by micro-Computerized Tomography (μCT) in accordance with the clinical evaluation standard. Lung pathological changes and collagen deposition were investigated by histopathology. Myofibroblast differentiation was assessed by immunohistochemistry of -SMA and TGF-β receptor type II expression in situ. Network pharmacology analysis of the drug-target interaction in IPF progression for DLP or DHP was performed using Ingenuity® Pathways Analysis (IPA) system. Results: We show that a non-invasive μCT effectively monitor and quantify BLM-induced pulmonary fibrosis and its treatment efficacy by Chinese medicine prescription in rodents. In addition, although both containing Salvia miltiorrhiza, DLP but not DHP mitigates BLM-induced lung fibrosis by inhibiting the TGF- signaling-activated myofibroblast differentiation and -SMA expression in a mouse model. Core analysis by IPA revealed that DLP ingredients regulated not only pulmonary fibrosis related inflammatory genes but also genes associated with myofibroblast activation and collagen deposition. Conclusion: This study suggests that a clinically efficacious cardiovascular Chinese herbal medicine (DLP) can be successfully repurposed to treat a lung disease in pulmonary fibrosis guided by TCM theory. Our comparative study between DLP and DHP demonstrated a critical requirement of suppressing both pro-inflammatory and pro-fibrotic pathways for the treatment of pulmonary fibrosis, supporting that a multi-component prescription capable of “removing both phlegm and blood stasis” will better achieve co-protection of heart and lung in pulmonary-heart disease.